Faktor-faktor yang Memengaruhi Perilaku Konsumsi Mahasiswa dan Estimasi Nilai Ekonomi Food Waste di Kantin Faperta - Chabibah, Chabibah; Rachmawati, Erna; Suminartika, Eti; Pardian, Pandi (Universitas Galuh, 2024)
Environmental problems in the form of waste generation globally have increased rapidly, one of which is food waste. Food waste generated will have an impact, both in the form of social, environmental and economic impacts. This study aims to determine (1) Factors that influence food waste consumption behavior of Padjadjaran University students in the BRI Faperta canteen (2) Estimating the value of food waste economic losses in the BRI Faperta canteen due to student food waste behavior. This research is a quantitative study with logistic regression analysis method and raw price approach (FDMM) and mature price approach to determine the estimated value of food waste losses incurred in the BRI Faperta canteen. Determination of respondents was carried out by purposive sampling method as many as 94 people who were consuming heavy food in the canteen. The results showed that there are factors that significantly influence food waste behavior in students in the BRI Faperta canteen, namely gender, habits, income and appetite. In addition, there is food waste that occurs with an estimated economic loss value in the BRI Faperta canteen of Rp1,437,420 / month with the raw weight approach and in the cooked weight approach of Rp2,532,981 / month, thus showing the percentage of economic losses in the BRI Faperta canteen which is 2.42%.